Managing Post-Disaster Socio-Economic Development: A Systematic Review of Strategies and Community Transformation - Achmad Fathor Rosyid; Amirul Wahid Ridlo Wicaksono Zain (Jurnal Ilmiah Manajemen Kesatuan, 2026)
Socio-economic changes in disaster-affected communities require effective development management to ensure the welfare of post-disaster populations. Communities that are unprepared for post-disaster development are vulnerable to falling into poverty and prolonged suffering that they did not anticipate. Therefore, this article aims to identify patterns of socio-economic impacts experienced by post-disaster communities in Indonesia as a basis for recommending more comprehensive and effective development strategies. This study employs a systematic literature review approach, using the Publish or Perish application as a tool for filtering and sorting relevant literature based on keywords related to changes, impacts, and strategies of post-disaster communities over the last ten years. The findings indicate that socio-economic changes in post-disaster communities show a distinct typology, which can be analyzed through strengths, weaknesses, opportunities, and challenges. The study concludes that post-disaster development should adopt a comprehensive, inclusive, and sustainable approach to effectively support the socio-economic recovery and long-term welfare of affected communities. The implication is that policymakers and development practitioners must implement targeted strategies to enhance both immediate recovery and long-term socio-economic resilience in affected communities.